Macroeconomic institutions and development - Neyapti, Bilin (Cheltenham, UK Edward Elgar, 2010)
This work by Bilin Neyapti, part textbook, part treatise, provides a synthesis of the relevant literature on macroeconomic institutions and development.
1. A modified approach to development economics -- 2. The model and empirics -- 3. Fiscal institutions and empirical evidence -- 4. Institutions of monetary policy and the financial sector.
Keywords: Macroeconomics; Economic development